İnşaat Mühendisi ve Amatör Matematikçi Aram Margosyan’ın İstatistik Üzerine Görüşleri - Bayam Takicak, Semiha Betül; Eden, Alp (Istanbul University, 2023)
After graduating from the École des Ponts et Chaussées in Paris, Aram Margossian (1853-1931) started working as an engineer in the Ottoman Ministry of Public Affairs, where he was later promoted to director of the railway administration. While working in this ministry, he lectured on mathematics and engineering at the Hendese-i Mülkiye, the school of civil engineering in Istanbul, and published books on these topics. In addition to his positions as a civil engineer, bureaucrat, and university teacher, he was also a distinguished amateur mathematician. Margosyan wrote a book on magic squares in French, which became the key to his fame. Part of Margosyan’s book was included in the French version of a book on recreational mathematics. Both books comprise what is known today as the Margossian Method. In his first paper published in the journal Sphinx-Œdipe, Margossian (1912) claimed to have solved an open problem. He also was one of the founders of Sphinx-Œdipe, a French journal of mathematics, at which point he sent two letters to the Journal of Ottoman Society of Engineers and Architects, in which he underlined the fact that he no longer was the director of the Ottoman Railways. The present article analyzes the content of these letters which he’d written after establishing his expertise in mathematics. The letters’ stress on the importance of statistical inference presents a good example of Margosyan’s deep understanding of mathematics. The current article also analyzes his views on the mathematical underpinnings of statistical inference and attempts to understand his rationale for writing these letters.

Aram Margosyan (1853-1931), Paris’teki École des Ponts et Chaussées’den (Köprüler ve Yollar Okulundan) mezun olduktan sonra Nafia Vekâleti’ne bağlı olarak Demiryolları’nda çalışmaya başlamış ve burada müdürlüğe kadar yükselmiştir. Nafia Vekâleti’nde çalışırken Hendese-i Mülkiye’de matematik ve mühendislik dersleri vermiş ve kitaplar yayınlamıştır. Osmanlı Türkiye’sindeki değişik görevlerinin yanı sıra Fransa’daki amatör matematikçiler grubu içinde kendine yer edinmiştir. Sihirli kareler konusundaki Fransızca kitabı, meşhur bir İngilizce eğlence matematiği kitabının Fransızca uyarlanması içinde alt bir bölüm olarak tekrar yayınlanmıştır. Margosyan, yurtdışındaki tanınmışlığını, “Margossian Method”u da içeren, bu esere borçludur. Fransız amatör matematikçi André Gérardin’in yönettiği Sphinx-Œdipe dergisinde yayınladığı ilk yazısında, Margosyan açık bir problemi çözdüğünü iddia etmiştir. Margosyan da Sphinx-Œdipe dergisinin kurucuları arasındadır. Osmanlı Mühendisler ve Mimarlar Cemiyeti Mecmuası’na, artık Osmanlı Demiryolları müdürü olmadığını vurguladığı iki mektup göndermiştir. Özellikle çıkarımsal istatistiğin önemini örneklerle anlatan mektubu, Margosyan’ın geniş bir matematik kültürünün göstergesidir. Bu makalemizde, Margosyan’ın hayatı hakkındaki bazı bilgileri sunduktan sonra istatistik yazısındaki görüşlerinin matematiksel içeriklerini değerlendirip bu yazıyı kaleme alma nedenini de anlamaya çalıştık.
Keywords: Aram Margosyan; Margossian; Statistical inference; History of mathematics; Magic squares; Euler’s officer problem; Ottoman Empire; Turkey; Aram Margosyan; Margossian; çıkarımsal istatistik; Matematik tarihi; Sihirli kareler; Euler subay problemi; Osmanlı İmparatorluğu; Türkiye; Aram Margosyan; Margossian; çıkarımsal istatistik; Matematik tarihi; Sihirli kareler; Euler subay problemi; Osmanlı İmparatorluğu; Türkiye; Aram Margosyan; Margossian; Statistical inference; History of mathematics; Magic squares; Euler’s officer problem; Ottoman Empire; Turkey